2017
DOI: 10.1007/s10157-017-1469-7
|View full text |Cite
|
Sign up to set email alerts
|

Allo-specific immune response profiles indicative of acute rejection in kidney allografts using an in vitro lymphocyte culture-based model

Abstract: Distinct post in vitro stimulation cytokine profiles at the time of transplantation thus correlated with the occurrence of post-transplantation rejection episodes which indicated feasibility of this in vitro model to assess the recipient's anti-graft response at an early stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Its subsequent cleavage to C3a and C3b fragments promotes the complement cascade and the C3a fragment functions as a significant anaphylatoxin, supporting the inflammatory processes ( 28 30 ). Recently, Mahakur et al discovered a significant difference in C3 expression in patients with antibody-mediated rejection, as compared to stable allograft results ( 31 ). In contrast, recent study confirmed earlier results suggesting that the decrease of C3 levels in serum is a potential predictive factor of poor renal prognosis in IgA nephropathy patients ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Its subsequent cleavage to C3a and C3b fragments promotes the complement cascade and the C3a fragment functions as a significant anaphylatoxin, supporting the inflammatory processes ( 28 30 ). Recently, Mahakur et al discovered a significant difference in C3 expression in patients with antibody-mediated rejection, as compared to stable allograft results ( 31 ). In contrast, recent study confirmed earlier results suggesting that the decrease of C3 levels in serum is a potential predictive factor of poor renal prognosis in IgA nephropathy patients ( 32 ).…”
Section: Discussionmentioning
confidence: 99%